2010
DOI: 10.1037/a0015727
|View full text |Cite
|
Sign up to set email alerts
|

Sense of belonging, sense of exclusion, and racial and ethnic identities in Korean transracial adoptees.

Abstract: Although many Korean transracial adoptees (KTAs) have White European American (WEA) family members, their racial features place them in the minority group. Thus, they navigate the meanings of race and culture from two reference groups: the majority WEA group and the Korean American group. This study explored the processes through which perceptions of group meanings and sense of belonging and exclusion related to the development of racial and ethnic identities. Fourteen adult KTAs in the Northeast participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 35 publications
(42 reference statements)
2
43
0
Order By: Relevance
“…This challenge of belongingness was also described by Hübinette (2004), who illuminated the idea of a "third space." The results of this study adhere to the findings from previous research on Korean transracial adoptees who have expressed their challenges to find a place where they truly fit in (Hübinette, 2004;Trenka, Oparah, & Shin, 2006;Kim, 2007;Kim, Suyemoto, & Turner, 2010). An important finding in this research is that the insufficiency of the sense of belongingness that adoptees experienced had changed over time.…”
Section: Lack Of Sense Of Belongingnesssupporting
confidence: 66%
“…This challenge of belongingness was also described by Hübinette (2004), who illuminated the idea of a "third space." The results of this study adhere to the findings from previous research on Korean transracial adoptees who have expressed their challenges to find a place where they truly fit in (Hübinette, 2004;Trenka, Oparah, & Shin, 2006;Kim, 2007;Kim, Suyemoto, & Turner, 2010). An important finding in this research is that the insufficiency of the sense of belongingness that adoptees experienced had changed over time.…”
Section: Lack Of Sense Of Belongingnesssupporting
confidence: 66%
“…C. Lee & Quintana, 2005; R. M. Lee et al, 2006;Yoon, 2004). Research on adult transnational adoptees also suggested that race and culture remain significant and complex parts of socialization (Sarubbi, Block-Learner, Moon, & Williams, 2012;Tigervall & Hübinette, 2010) and can apply to the adoptees' sense of belonging and exclusion from both majority and ethnic minority groups (Kim et al, 2010).…”
Section: Complexities Of Transnational and Adoptee Identitymentioning
confidence: 99%
“…M. Lee, 2003). KADs also face racial discrimination as visible minorities (Docan-Morgan, 2010;Feigelman, 2000;Freundlich & Lieberthal, 2000) and challenges to their ethnic heritage (Kim, Suyemoto, & Turner, 2010;Shiao & Tuan, 2008). Although not all KADs and other transnational adoptees will seek counseling services, those who do may struggle to find multiculturally competent counselors who also recognize the complexity of adoption throughout the life span.…”
mentioning
confidence: 99%
“…A similar story may be true for those adopted by parents with different racial/ethnic backgrounds. Feelings of group belonging among Korean children adopted by White parents (and others like them) are particularly influenced by others, culture, and reflected appraisals of the way they look (Kim, Suyemoto, & Turner, 2010). Harris and Sim (2002) found that those not living with their biological parents were more likely than others in their sample to connect with multiple racial and ethnic groups.…”
Section: Resultsmentioning
confidence: 99%